Thick film negative photoresist as well as preparation method and application thereof
By designing thick film negative photoresist containing specific acrylic resins and other components, the problem of insufficient thickness and electroplating resistance in the copper bump process is solved, and high film thickness, uniformity and resistance are achieved. Comprehensive performance of electroplating.
Patent Information
- Application Number
- CN202411532301.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-11
AI Technical Summary
Traditional positive photoresist cannot be coated to a thickness of 80μm, and is prone to cracking and plating during the electroplating process, which cannot meet the requirements of the copper bump process.
A thick film negative photoresist is designed, which includes acrylic resins with specific structures, crosslinking agents, initiators, leveling agents and defoaming agents. Through the combined action of these components, a thick film with excellent performance is prepared. Negative photoresist.
With a coating thickness of 80 μm, the photoresist does not require post-drying after patterning. It can keep the rubber surface intact when electroplating copper, nickel, and selenium silver, without cracking and plating, and is easily removed after electroplating without residue.
Smart Images

Figure CN119414658A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoresists for chip packaging, and in particular relates to a thick film negative photoresist and a preparation method and application thereof. Background Art
[0002] Copper bump is a manufacturing technology that uses copper pillar bonding instead of wire bonding to achieve electrical interconnection between chip and substrate. Copper pillar bump technology is a new generation of chip interconnection technology. The back-end is suitable for flip-chip (FC) packaging and is widely used. Its process includes cleaning and preparation of incoming wafers, preparation of PI polyimide layer, preparation of UBM (Under Bump Metallization) under-bump metallization layer, preparation of thick photoresist pattern, copper pillar electroplating Cu Pillar (ECDElectrochemical Deposition), electroplating nickel Ni Barrier (ECD), electroplating tin cap Solder (ECD), photoresist removal, seed layer removal, reflow and other steps.
[0003] In the copper bump process, photoresist mainly plays the role of mask. The proportion of acrylic resin in photoresist is relatively large, which mainly plays the role of photoresist frame. Its main structure and molecular weight play a key role in the electroplating resistance of photoresist. Its molecular weight plays a decisive role in the film thickness of photoresist. Traditional positive photoresist cannot be coated to a thickness of 80μm due to its limited molecular weight. Moreover, due to the relatively high hardness of traditional positive phenolic series photoresist, it is easy to crack and infiltrate in the electroplating solution, which cannot meet the electroplating process of copper bump. In negative thick film photoresist, under the action of crosslinker and initiator, UV light crosslinking increases the crosslinking density of photoresist, improves the steepness and resolution of negative photoresist graphics, and meets the requirements of copper bump process. Leveling agent mainly plays the role of coating leveling characteristics of photoresist. Under the coating requirement of 80μm, the type and amount of leveling agent determine the coating uniformity of photoresist with high film thickness at low spin speed. Due to the high film thickness, when the photoresist is baked, the surface of the photoresist is easy to dry due to solvent volatilization. The solvent in the underlying photoresist cannot "escape" and bubbles are formed in the photoresist layer. Therefore, a defoaming agent needs to be added to the photoresist to eliminate bubbles during baking.
[0004] Therefore, how to provide a photoresist with excellent performance that can be used to prepare copper bumps has become a technical problem that needs to be solved urgently. Summary of the invention
[0005] In view of the deficiencies of the prior art, the object of the present invention is to provide a thick film negative photoresist and a preparation method and application thereof. The present invention designs the composition of the thick film negative photoresist, and through the joint action of each component, a thick film negative photoresist with excellent performance is prepared. The thick film negative photoresist is used in the copper bump process of the advanced packaging industry. When the coating film thickness reaches 80 μm, after patterning, no post-baking is required. The electroplating of copper, nickel, and selenium silver is performed in between. During the electroplating, the photoresist surface is intact without cracking and infiltration. After electroplating, the photoresist is easy to remove without residue.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a thick film negative photoresist, wherein the thick film negative photoresist comprises the following components in percentage by weight:
[0008]
[0009] The thick film negative photoresist also includes a leveling agent and a defoaming agent;
[0010] The mass concentration of the leveling agent in the thick film negative photoresist is 500-1500ppm;
[0011] The mass concentration of the defoamer in the thick film negative photoresist is 300-1000ppm;
[0012] The acrylic resin comprises a structure as shown in the following formula:
[0013] n≥1 (for example, it can be 1, 2, 5, 8, 10, 15, 20, 22, 25, 27, 30, 33, 36, 40, 42, 46, 47, 50, 52, 55 or 60, etc.).
[0014] The invention designs the composition of thick film negative photoresist and prepares a thick film negative photoresist with excellent performance through the joint action of various components in specific amounts. The thick film negative photoresist is used in the copper bump process of the advanced packaging industry. When the coating film thickness reaches 80 μm, after patterning, no post-baking is required. The electroplating of copper, nickel, and selenium silver is performed. During electroplating, the photoresist surface is intact without cracking and infiltration plating. After electroplating, the photoresist is easy to remove without residue.
[0015] In the present invention, a thick film negative photoresist with excellent performance is prepared by using an acrylic resin with a specific structural formula. The bonding force between the photoresist and the substrate copper is improved by setting the carboxyl group in the acrylic resin. The dissolution of the acrylic resin in an alkaline developer can be improved by setting the hydroxyl group and its content.
[0016] In the present invention, the comprehensive performance of the thick film negative photoresist is further improved by controlling the amount of the defoamer within a specific range. The defoamer can reduce the surface tension of the thick film negative photoresist and improve the fluidity of the photoresist. For anti-electroplating, the resin itself needs a certain molecular weight. The defoamer has a relatively small molecular weight and is evenly filled in the photoresist, which is not resistant to electroplating. Therefore, if the amount of the defoamer is too large, it will affect the electroplating characteristics, which will cause the thick film negative photoresist to be plated when electroplated in the copper bump process of the advanced packaging industry. If the amount of the defoamer is too small, the fluidity of the thick film negative photoresist will be poor.
[0017] In the present invention, the mass percentage of acrylic resin in the thick film negative photoresist is 30%, 32%, 33%, 35%, 36%, 38%, 40%, 41%, 42%, 43%, 44% or 45%, etc.
[0018] The mass percentage of the crosslinking agent in the thick film negative photoresist is 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, etc.
[0019] The mass percentage of the initiator in the thick film negative photoresist is 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%, etc.
[0020] The mass percentage of the solvent in the thick film negative photoresist is 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49% or 50%, etc.
[0021] The mass concentration of the leveling agent in the thick film negative photoresist is 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm or 1500ppm, etc.
[0022] The mass concentration of the defoaming agent in the thick film negative photoresist is 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm or 1000ppm, etc.
[0023] It should be noted that the "thick film" in the thick film negative photoresist provided by the present invention means that when the thick film negative photoresist is used in the copper bump process of the advanced packaging industry, the coating film thickness can reach 80μm.
[0024] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0025] As a preferred technical solution of the present invention, the raw materials for preparing the acrylic resin include the following components:
[0026] p-Hydroxystyrene, acrylic acid, styrene;
[0027] Preferably, the mass ratio of p-hydroxystyrene, acrylic acid and styrene is 6:(4-5):(5-6), for example, it can be 6:4:5, 6:4.5:5, 6:5:5, 6:4:5.5, 6:4:6, 6:4.5:5.5, 6:4.5:6, 6:5:5.5 or 6:5:6, etc.
[0028] Preferably, the acrylic resin is prepared by the following method, which comprises the following steps:
[0029] The acrylic resin is obtained by mixing p-hydroxystyrene, acrylic acid, styrene and a solvent and polymerizing them.
[0030] Preferably, the initiator comprises azobisisobutyronitrile.
[0031] Preferably, the solvent comprises propylene glycol methyl ether acetate (PGMEA).
[0032] It should be noted that the present invention does not have any special requirements for the specific amount of the initiator solvent, and the commonly used amount ranges in the art are applicable. For the initiator, its amount exemplarily includes but is not limited to: based on the mass of the p-hydroxystyrene as 100%, the mass percentage content of the initiator is 1-3% (for example, it can be 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8% or 3%, etc.); for the solvent, its amount exemplarily includes but is not limited to: based on the mass of the p-hydroxystyrene as 100%, the mass percentage content of the solvent is 350-450% (for example, it can be 350%, 360%, 370%, 380%, 390%, 400%, 410%, 420%, 430%, 440% or 450%, etc.).
[0033] Preferably, the polymerization temperature is 80-90°C (for example, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, etc.), and the time is 2-4h (for example, 2h, 2.5h, 3h, 3.5h or 4h, etc.).
[0034] Preferably, the polymerization reaction further includes a post-treatment step, and the post-treatment method includes: cooling the polymerized product to room temperature, placing it in water to precipitate solid matter, filtering, and drying.
[0035] Preferably, the drying method comprises vacuum drying.
[0036] Preferably, the acrylic resin is prepared by the following method, which specifically comprises the following steps:
[0037] Para-hydroxystyrene, acrylic acid, styrene, an initiator and a solvent are mixed, polymerized at 80-90° C. for 2-4 hours, the polymerized product is cooled to room temperature, placed in water to precipitate solid matter, filtered and dried to obtain the acrylic resin.
[0038] Preferably, the number average molecular weight of the acrylic resin is 5000-12000, for example, 5000, 5500, 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500, 10000, 11000 or 12000, etc.
[0039] Preferably, the polydispersity coefficient of the acrylic resin is 1.3-12.0, for example, it can be 1.3, 1.5, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0 or 12.0, etc.
[0040] It should be noted that, in the present invention, the polydispersity coefficient is the ratio of the weight average molecular weight to the number average molecular weight.
[0041] As a preferred technical solution of the present invention, the crosslinking agent is selected from any one of divinyl ether, 2-ethoxyethyl vinyl ether, 1,1-diethoxyethylene or perfluoroethyl vinyl ether, or a combination of at least two thereof.
[0042] As a preferred technical solution of the present invention, the initiator includes a photoinitiator.
[0043] Preferably, the photoinitiator is selected from 1-[4-(phenylthio)phenyl]-1,2-octanedione-2-(O-benzoyl oxime) and / or 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone-1-(O-acetyl oxime).
[0044] As a preferred technical solution of the present invention, the defoaming agent includes an organosilicon polymer.
[0045] Preferably, the organic silicon polymer includes an organic silicon polymer of model A530 produced by BYK.
[0046] As a preferred technical solution of the present invention, the leveling agent includes an ethylene glycol copolymer surfactant.
[0047] Preferably, the leveling agent includes DC57 leveling agent produced by Dow Corning.
[0048] As a preferred technical solution of the present invention, the solvent includes propylene glycol methyl ether acetate and / or propylene glycol methyl ether.
[0049] In the present invention, the comprehensive performance of the thick film negative photoresist is further improved by optimizing the specific selection of each component and using a specific acrylic resin, a crosslinking agent, an initiator, a leveling agent and a defoaming agent.
[0050] In a second aspect, the present invention provides a method for preparing the thick film negative photoresist as described in the first aspect, the preparation method comprising the following steps:
[0051] The components of the thick film negative photoresist are mixed to obtain the thick film negative photoresist.
[0052] In a third aspect, the present invention provides a use of the thick film negative photoresist as described in the first aspect, wherein the thick film negative photoresist is used to prepare copper bumps.
[0053] As a preferred technical solution of the present invention, the thick film negative photoresist is used for preparing thick photoresist patterns in the copper bump preparation process.
[0054] Preferably, the thick film negative photoresist is used in the copper bump preparation process, and the coating thickness of the thick film negative photoresist is ≥80μm (for example, it can be 80μm, 81μm, 84μm, 86μm, 88μm, 92μm, 94μm, 97μm, 100μm, 102μm, 105μm, 108μm, 110μm, 112μm, 114μm, 116μm, 118μm, 120μm, 124μm, 128μm or 130μm, etc.), and is further preferably 110-120μm.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] (1) The present invention designs the composition of thick film negative photoresist, and prepares a thick film negative photoresist with excellent performance through the joint action of various components. The thick film negative photoresist is used in the copper bump process of the advanced packaging industry. When the coating film thickness reaches 80 μm, after patterning, no post-baking is required. The electroplating of copper, nickel, and selenium silver is performed in between. During electroplating, the photoresist surface is intact without cracking and infiltration plating. After electroplating, the photoresist is easy to remove without residue.
[0057] (2) The thick film negative photoresist provided by the present invention is used in the copper bump process of the advanced packaging industry. When the coating film thickness reaches 80 μm, the coating uniformity is controlled within 5%, the resolution reaches 20 μm, the angle is steep, and it is resistant to copper, nickel, and selenium silver electroplating. The adhesive surface is intact and not infiltrated, and the photoresist is easy to remove after electroplating. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 The thick film negative photoresist provided in Example 1 of the present invention is coated on an 8-inch silicon wafer by spin coating, with a coating thickness of 80 μm. After coating, it is baked and hardened, exposed, and developed to obtain the required pattern, and then electroplated, and finally the photoresist is removed to obtain the required electroplated pattern. DETAILED DESCRIPTION
[0059] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0060] The sources of some components in the following examples and comparative examples are as follows:
[0061] Acrylic resin 1: p-Hydroxystyrene (120 g), acrylic acid (90 g), styrene (110 g), azobisisobutyronitrile (0.5 g) and propylene glycol methyl ether acetate (400 g) were mixed and polymerized at 85° C. for 3 h. The polymerized product was cooled to room temperature and placed in water to precipitate solid matter. The solid matter was filtered and dried in an empty oven at 45° C. for 96 hours to obtain an acrylic resin. The acrylic resin was tested by gel permeation chromatography, and the number average molecular weight and polydispersity coefficient of the acrylic resin were 11,000 and 1.65.
[0062] Acrylic resin 2: purchased from Mitsubishi Corporation, BR-10.
[0063] The sources of other components are shown in Table 1 below:
[0064] Table 1
[0065] Components illustrate Crosslinker 1 divinyl ether Crosslinker 2 2-Ethoxyethyl vinyl ether Crosslinker 3 1,1-Diethoxyethylene Crosslinker 4 Perfluoroethyl vinyl ether Photoinitiator 1 1-[4-(Phenylthio)phenyl]-1,2-octanedione-2-(O-benzoyl oxime) Photoinitiator 2 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone-1-(O-acetyl oxime) Solvent 1 Propylene glycol methyl ether acetate Solvent 2 Propylene glycol methyl ether Leveling agent Silicone polymer, purchased from BYK, model A530 Defoaming agent Purchased from Dow Corning, model number DC57
[0066] Example 1-Example 7, Comparative Examples 1-3
[0067] Examples 1-7 and Comparative Examples 1-3 respectively provide a thick film negative photoresist and a preparation method thereof. The specific composition of the thick film negative photoresist is shown in Table 2 below, wherein the amounts of acrylic resin, crosslinking agent, initiator and solvent are all weight parts, and the amounts of leveling agent and defoaming agent are all mass concentrations in the thick film negative photoresist;
[0068] The preparation method of the above thick film negative photoresist is as follows:
[0069] The components of the thick film negative photoresist are mixed to obtain the thick film negative photoresist.
[0070] Table 2
[0071]
[0072] The following properties of the thick film negative photoresists provided in the above embodiments and comparative examples were characterized, and the specific testing methods are as follows:
[0073] The thick film negative photoresists provided in the above embodiments and comparative examples are respectively coated on an 8-inch silicon wafer by spin coating, with a coating thickness of 80 μm. After coating, they are baked and hardened at 120° C. for 5 min, exposed, and developed to obtain the desired pattern, and then electroplated, and finally the photoresist is removed to obtain the desired electroplated pattern;
[0074] The thickness of the coated photoresist film was tested by using a film thickness meter F20 from Filmetrics. The coating method was as follows: the photoresist was coated using a coating machine AC-200 from Jiangyin Leibo Co., Ltd. The hot plate for baking was DNK-2K from AS ONE Co., Ltd.
[0075] Flow uniformity: Flow uniformity = (thickness value of the thickest part of the photoresist film after coating - thickness value of the thinnest part of the photoresist film) ÷ thickness value of the thinnest part of the photoresist film × 100%;
[0076] Bubbles: The number of bubbles after coating was observed using a BX-53 microscope produced by Olympus;
[0077] Angle after electroplating: After electroplating, put the electroplated wafer into the degumming solution, heat it to 50℃, keep it for 20min, then wash it with water for 2min, blow it dry with nitrogen, and use a scanning electron microscope (SEM) to observe the morphology of the electroplated pattern and measure the height, width and angle of the pattern;
[0078] Electroplating characteristics: After removing the photoresist, place it under a microscope to observe whether there is any seepage. If the photoresist surface turns abnormally white, or the base copper turns black, it means that there is seepage. If there is no seepage, record it as "OK";
[0079] Resolution: Characterized using a BX-53 microscope (1000x magnification metallographic microscope) produced by Olympus;
[0080] Comprehensive evaluation: If the above performance measurements all meet the standards, they will be recorded as "OK", otherwise, they will be recorded as "NG".
[0081] The above performance test results are shown in Table 3 below.
[0082] Table 3
[0083] Flow uniformity bubble Angle after electroplating (°) Electroplating characteristics Resolution Comprehensive Assessment standard <5% No bubbles ≥87 No plating ≥40μm Example 1 3.23% none 88 OK 42μm OK Example 2 3.45% none 89 OK 72μm OK Example 3 2.02% none 89 OK 80μm OK Example 4 4.83% none 87 OK 44μm OK Example 5 3..32% none 90 OK 102μm OK Example 6 4.02% none 88 OK 41μm OK Example 7 2.23% none 88 OK 42μm OK Comparative Example 1 8.23% none 32 Plating 65μm NG Comparative Example 2 8.46% many 87 OK 72μm NG Comparative Example 3 7.84% none 89 Slightly permeated 43μm NG
[0084] The electroplating pattern prepared by the thick film negative photoresist provided in Example 1 of the present invention is as follows: Figure 1 As shown by Figure 1 It can be seen that the comprehensive performance of the thick film negative photoresist provided in Example 1, such as coating uniformity, bubbles, electroplating angle, and electroplating resistance, meets the design content of the present invention.
[0085] As can be seen from the above content, the present invention designs the composition of thick film negative photoresist, and through the joint action of various components, a thick film negative photoresist with excellent performance is prepared. The thick film negative photoresist is used in the copper bump process of the advanced packaging industry. When the coating film thickness reaches 80 μm, after patterning, no post-baking is required. The electroplating of copper, nickel, and selenium silver is performed in between. During electroplating, the photoresist surface is intact without cracking and infiltration plating. After electroplating, the photoresist is easy to remove without residue.
[0086] The thick film negative photoresist provided by the present invention is used in the copper bump process of the advanced packaging industry. When the coating film thickness reaches 80 μm, the uniformity of the coating flow is controlled within 5%, the resolution reaches 40 μm, there are no bubbles, the angle is steep (the angle after electroplating is ≥87°), it is resistant to copper, nickel, and selenium silver plating, the adhesive surface is complete and not infiltrated, and the photoresist is easy to remove after electroplating.
[0087] It can be seen from Examples 1-7 and Comparative Example 1 that the present invention prepares a thick-film negative photoresist with excellent performance by selecting an acrylic resin with a specific structure.
[0088] It can be seen from Example 1, Examples 6-7 and Comparative Examples 2-3 that the present invention further improves the electroplating characteristics of the thick film negative photoresist by designing the dosage of the defoaming agent.
[0089] In summary, the present invention designs the composition of thick film negative photoresist, and prepares a thick film negative photoresist with excellent performance through the joint action of various components. The thick film negative photoresist is used in the copper bump process of the advanced packaging industry. When the coating film thickness reaches 80 μm, after patterning, no post-baking is required, and the electroplating of copper, nickel, and selenium silver is performed. During electroplating, the photoresist surface is intact without cracking and infiltration plating. After electroplating, the photoresist is easy to remove without residue.
[0090] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A thick film negative photoresist, characterized in that The thick film negative photoresist comprises the following components in percentage by weight: The thick film negative photoresist also includes a leveling agent and a defoaming agent; The mass concentration of the leveling agent in the thick film negative photoresist is 500-1500ppm; The mass concentration of the defoamer in the thick film negative photoresist is 300-1000ppm; The acrylic resin comprises a structure as shown in the following formula:
2. The thick film negative photoresist according to claim 1, characterized in that The raw materials for preparing the acrylic resin include the following components: p-Hydroxystyrene, acrylic acid, styrene; Preferably, the mass ratio of p-hydroxystyrene, acrylic acid and styrene is 6:(4-5):(5-6); Preferably, the acrylic resin is prepared by the following method, which comprises the following steps: mixing p-hydroxystyrene, acrylic acid, styrene, an initiator and a solvent, and polymerizing to obtain the acrylic resin; Preferably, the initiator comprises azobisisobutyronitrile; Preferably, the solvent comprises propylene glycol methyl ether acetate; Preferably, the polymerization temperature is 80-90°C and the time is 2-4h; preferably, the number average molecular weight of the acrylic resin is 5000-12000; Preferably, the polydispersity coefficient of the acrylic resin is 1.3-12.
0.
3. The thick film negative photoresist according to claim 1 or 2, characterized in that: The crosslinking agent is selected from any one of divinyl ether, 2-ethoxyethyl vinyl ether, 1,1-diethoxyethylene or perfluoroethyl vinyl ether, or a combination of at least two thereof.
4. The thick film negative photoresist according to any one of claims 1 to 3, characterized in that: The initiator comprises a photoinitiator; Preferably, the photoinitiator is selected from 1-[4-(phenylthio)phenyl]-1,2-octanedione-2-(O-benzoyl oxime) and / or 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone-1-(O-acetyl oxime).
5. The thick film negative photoresist according to any one of claims 1 to 4, characterized in that: The defoaming agent includes a silicone polymer.
6. The thick film negative photoresist according to any one of claims 1 to 5, characterized in that: The leveling agent includes an ethylene glycol copolymer surfactant.
7. The thick film negative photoresist according to any one of claims 1 to 6, characterized in that: The solvent includes propylene glycol methyl ether acetate and / or propylene glycol methyl ether.
8. A method for preparing a thick film negative photoresist as claimed in any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The components of the thick film negative photoresist are mixed to obtain the thick film negative photoresist.
9. A use of the thick film negative photoresist according to any one of claims 1 to 7, characterized in that: The thick film negative photoresist is used to prepare copper bumps.
10. The use according to claim 9, characterized in that: The thick film negative photoresist is used for preparing thick photoresist patterns in the copper bump preparation process; Preferably, the thick film negative photoresist is used in the copper bump preparation process, and the coating thickness of the thick film negative photoresist is ≥80 μm, and more preferably 110-120 μm.